1998
DOI: 10.1111/j.1574-6968.1998.tb13179.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bounded nucleoids in microbial symbionts of marine sponges

Abstract: In thin sections of resin‐embedded samples of glutaraldehyde‐ and osmium tetroxide‐fixed tissue from five genera of marine sponges, Stromatospongia, Astrosclera, Jaspis, Pseudoceratina and Axinyssa, cells of a bacteria‐like symbiont microorganism which exhibit a membrane‐bounded nuclear region encompassing the fibrillar nucleoid have been observed within the sponge mesohyl. The nuclear region in these cells is bounded by a single bilayer membrane, so that the cell cytoplasm is divided into two distinct regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Morphotype 6 contains characteristic bleblike structures. Previous reports showed that in morphotypes 1 to 5, the fibrillar DNA is located in the nucleoid, while in morphotype 6, the RNA is contained in the nucleoid and the DNA is located in the cytoplasm (17). Morphotype 6 shows some resemblance to Gemmatimonas aurantiaca, the first cultivated representative of the novel phylum Gemmatimonadetes (56).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Morphotype 6 contains characteristic bleblike structures. Previous reports showed that in morphotypes 1 to 5, the fibrillar DNA is located in the nucleoid, while in morphotype 6, the RNA is contained in the nucleoid and the DNA is located in the cytoplasm (17). Morphotype 6 shows some resemblance to Gemmatimonas aurantiaca, the first cultivated representative of the novel phylum Gemmatimonadetes (56).…”
Section: Discussionmentioning
confidence: 89%
“…Altogether, six different morphotypes were found that closely resemble the different subtypes of Australian Great Barrier Reef sponges ( Fig. 3; Table 2) (16,17). Five of the morphotypes contain a membrane-bound organelle that occupies a central position in the cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were detected in the water column and sediments of fresh water lakes (Neef et al, 1998;Miskin et al, 1999;Wang et al, 2002;Kalyuzhnaya et al, 2004Kalyuzhnaya et al, , 2005a, hot springs (Giovannoni et al, 1987a), in the water column (DeLong et al, 1993;Vergin et al, 1998;Gade et al, 2004) as well as in shallow and deep sea sediments of marine systems (LlobetBrossa et al, 1998;Rusch et al, 2003;Inagaki et al, 2006;Musat et al, 2006) and in oxic and anoxic soils (Wang et al, 2002). Furthermore, planctomycetes have been detected in marine sponges (Fuerst et al, 1998Pimentel-Elardo et al, 2003) and in the hepatopancreas of the crustacean Panaeus monodon (Fuerst et al, 1991, in freshwater (Crump et al, 1999), marine detritus particles (DeLong et al, 1993;Fuerst, 1995;Crump et al, 1999) and attached to diatoms (Morris et al, 2006).…”
Section: Introductionmentioning
confidence: 99%